“Here’s Some Money, Your Work’s So Worthy?” A Brief Report on the Validation of the Functional Meaning of Cash Rewards Scale - Thibault Landry, Anaïs; Papachristopoulos, Konstantinos; Gradito Dubord, Marc-Antoine; Forest, Jacques (Frontiers in Psychology, 2022)
In the present research, we validated a new scale developed from Self-Determination Theory (SDT) to assess the functional meaning of cash rewards offered in the workplace. According to SDT, rewards can take on different meanings based on the way they are perceived by individuals. In a series of three studies in different socioeconomic contexts, we replicated the two-factorial structure of the scale measuring respectively workplace cash rewards’ informative and controlling meanings. In Study 1, we validated the English version of the scale by exploring and then confirming its 2-factor structure with two English-speaking employee samples. We further replicated its 2-factor structure in a French-speaking employee sample of employees in Study 2 and in a Greek-speaking employee sample in Study 3, allowing us to validate its French and Greek version. Results from our three studies show how distinct meanings attributed to cash rewards, i.e., informative or controlling, relate differently to autonomous and controlled forms of motivation based on SDT. These findings suggest that workplace cash rewards differently influence employees’ motivation depending on whether they are perceived as informative or controlling, thus providing empirical evidence for the theoretical and practical implications of SDT’s concept of functional meaning of cash rewards. Our research contributes to the assessment and understanding of employees’ experience of workplace cash rewards and provides empirical evidence that the concept of the functional meaning of cash rewards is a distinct concept from other money-related concepts such as subjective pay satisfaction, performance-contingent rewards, and financially-contingent self-worth.